Gestão do risco cambial via instrumentos de derivativos: estudo de caso de uma empresa do setor automotivo - Martinho, Mauricio José Afonso (2005)
During the last six years, the exchange rate in Brazil has been presenting a high volatility, mainly due to the end of exchange rate fixing, in the beginning of 1999, and due to the consequently implementation of a policy which provided the exchange rate prices flexibility. Within this context, companies that hold assets and liabilities linked to the exchange rate variation, and do not have a hedge policy, will be liable to the exchange rate risk exposure, that is, their financial results tend to present straight dependence to the exchange rate variation. One of the manners to reduce the exchange rate risk exposure is the utilization of derivatives instruments, which internal market negotiations also presented a meaningful increase, during the period mentioned above. The applying of these deals in the exchange rate risk management is the main objective of these research. Thus, it was looked for a methodology which considers quantitative and qualitative variables aiming to confirm the effectiveness of the derivatives deals in reducing the exposure to the exchange rate volatility. To achieve this objective, it was developed a research that can be divided in two main steps. Firstly, it was obtained, by a bibliographic search, the mainly characteristics of the derivative instruments linked to exchange rate, considering the national market, as well as the financial risk management importance in companies that present exchange rate risk exposure. Secondly, it was selected a case study research which considers all hedge transactions done by an automotive company, performing in the internal market, and also the assets and liabilities that motivate these deals as from 1998, period in which the company began to present an exposure increase to the exchange rate volatility. At the end, the analysis of the hedge transactions results combined to the products of the assets and liabilities, object of the protections, demonstrated that the objectives defined in the beginning of the deals by the company were attained, meaning that the derivative instruments revealed themselves as efficient tools to the company exchange rate risk management